The Role of The Listener and Government Institutions in Educational Radio Broadcasts (Peran Serta Pendengar dan Lembaga Pemerintah dalam Siaran Radio Pendidikan) - nfn Innayah; Mariana Susanti (BBPSDMP KOMINFO MAKASSAR, 2016)
The participation of the partner radio stations based on previous studiy still are nonparticipation, it means that the radio station just do what is stated in the agreement to broadcast educational content BPMRPK development results on the schedule that was agreed upon. The lack of radio station partners in partnership with educational institutions is also one of the causes of low participation. This study is a continuation of previous research which aims to describe the role as well as listener and Government agencies in educational radio broadcasts. This study aims to describe the role as well as listener and Government agencies in educational radio broadcasts. The method used was a survey. The population of the research was the radio station partners that totaled 57, 38 samples of an active partner radio stations broadcast educational content developed by BPMRP. The results showed that participation or the participation of the listeners and Government agencies in the broadcast radio education is low. This is due, among others, lack of empowerment of the radio listeners in accommodating the aspirations of the community and the radio stations that have yet to truly serve the needs of the information society in the communication and interaction, especially education.Partisipasi stasiun radio mitra berdasarkan penelitian sebelumnya masih bersifat nonparticipation. Hal ini berarti stasiun radio hanya melakukan apa yang tertuang dalam perjanjian kerja sama untuk menyiarkan konten-konten pendidikan hasil pengembangan BPMRPK sesuai jadwal yang disepakati. Kurangnya stasiun radio mitra dalam menjalin kerja sama dengan lembaga pendidikan juga merupakan salah satu sebab rendahnya partisipasi tersebut. Penelitian ini merupakan kelanjutan dari penelitian sebelumnya yang bertujuan untuk mendeskripsikan peran serta pendengar dan lembaga pemerintah dalam siaran radio pendidikan. Metode yang digunakan adalah survei dengan jumlah populasi sebanyak 57 stasiun radio mitra dan sampel sebanyak 38 stasiun radio mitra, yang masih aktif menyiarkan konten pendidikan yang dikembangkan oleh BPMRP. Hasil penelitian menunjukkan bahwa peran serta atau partisipasi pendengar dan lembaga pemerintah dalam siaran radio pendidikan masih tergolong rendah. Hal ini disebabkan antara lain kurangnya pemberdayaan pendengar oleh pihak radio dalam menampung aspirasi masyarakat, dan stasiun radio belum bersungguh-sungguh melayani kebutuhan informasi dan interaksi komunikasi masyarakat, khususnya siaran pendidikan.